Structure and morphology of relic galaxies in the Local Universe. Issue Volume 15:Issue S359(2020) (March 2019) - Freitas, Rodrigo F.; Chies-Santos, Ana L.; Furlanetto, Cristina; Ferrari, Fabricio
Abstract: Red Nugget galaxies found at high-z have analogues in the Local Universe which are called relic galaxies. Because of their proximity to Earth, the relics allow a more detailed analysis of their properties and can help us understand the formation of massive early-type galaxies, since Red Nuggets could be their first phase of formation. The main goal of this work is to characterize the structure and morphology of candidates and confirmed relic galaxies in the Local Universe to further search for similar objects observationally and within cosmological simulations.